Lime and calcium-magnesium silicate cause chemical attributes stratification in no-till fields - Antonangelo, João Arthur; Neto, Jayme Ferrari; Crusciol, Carlos Alexandre Costa [UNESP]; Zhang, Hailin; Alleoni, Luís Reynaldo F. (Elsevier, 2022)
The stratification of soil chemical properties under long-term no-till (NT) where different soil pH regimes are used and at different cropping-systems (CS) has yet to be studied. We aimed to evaluate the effect of the surface application of soil pH amendments on soil chemical attributes of stratified soil samples and their relationship with the subsequent yield of the soybean crop. The effect of the surface application of lime and calcium-magnesium silicate (CMS) on the chemical attributes of soil samples with increment depth (0–5, 5–10, 10–20, 20–40, and 40–60 cm) was evaluated. Also, their relationships with the subsequent soybean (Glycine max) yield on a tropical acidic soil under NT with four CS (SB: soybean─Brachiaria brizantha; SC: soybean─Crotalaria spectabilis; SF: soybean─fallow; and SW: soybean─ Triticum aestivum) were compared. The NT operations caused the stratification of all soil chemical attributes studied regardless of the CS and soil pH amendment. Application of lime or CMS significantly decreased exchangeable aluminum (Al) and potential acidity (H+Al), and increased pH, calcium (Ca), magnesium (Mg), silicon (Si), the sum of base (SB), and base saturation (BS%) in the upper soil layers (up to 10 cm) for most CS studied. Soil acidity parameters from 0 to 5 cm were related to soybean yield, and the stratification of H+Al led to a difference of 2-ton ha-1 soil amendment needed (p < 0.001) when soil is sampled from 0 to 5 cm in comparison to the 0–20 cm sampling.
Keywords: Lime Application; Long-term No-till; Silicate; Soil Chemical Attributes; Stratification Effects